Video tamper detection method based on nonnegative tensor factorization - Xue-li ZHANG; Tian-qiang HUANG; Jing LIN; Wei HUANG (网络与信息安全学报)
The authenticity and integrity of video authentication is one of the important contents in information security field.A video tampering detection method based on non-negative tensor decomposition was proposed for video inter-frame tampering.First of all,spectral feature of video frame was extracted quickly.The video was described by a three-dimensional tensor which created by the main compression feature.The tensor was factorized by Tucker non-negative decomposition method and then the time dimension matrix was extracted to calculate correlation.Finally,the tampering position was determined by using the Chebyshev’s inequality.Experiments show that this method can detect the video inter-frame tampering quickly and robustly.